Changes in Conjunctiva Morphology Using Impression Cytology in Patients with Hashimoto's Thyroiditis without Thyroid-Associated Ophthalmopathy - Mustafa ALTAY (Türk Patoloji Dergisi, 2019)

(untitled)
Objective: To compare the conjunctival morphological changes in patients with Hashimotos thyroiditis (HT) without thyroid-associated ophthalmopathy (TAO) and controls using impression cytology technique.